2015
DOI: 10.3390/ijms160817719
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Stability & Conformational Changes in β-Lactoglobulin: Unfolding to Self-Assembly

Abstract: A detailed understanding of the mechanism of unfolding, aggregation, and associated rheological changes is developed in this study for β-Lactoglobulin at different pH values through concomitant measurements utilizing dynamic light scattering (DLS), optical microrheology, Raman spectroscopy, and differential scanning calorimetry (DSC). The diffusion interaction parameter kD emerges as an accurate predictor of colloidal stability for this protein consistent with observed aggregation trends and rheology. Drastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The volume size distribution of βlg (at 0.5 and 1.5% w/w) in SIF was determined in a previous work (Naso et al 2018). A monomodal particle size distribution was obtained, with a maximum value at 4.6 nm, which falls in between those corresponding to the monomeric (3.6 nm) and the dimeric form (6.9 nm) (Blake, Amin, Qi, Majumda, & Lewis, 2015).…”
Section: Oleic Acid Solubilization In the Presence Of β-Lactoglobulinmentioning
confidence: 98%
“…The volume size distribution of βlg (at 0.5 and 1.5% w/w) in SIF was determined in a previous work (Naso et al 2018). A monomodal particle size distribution was obtained, with a maximum value at 4.6 nm, which falls in between those corresponding to the monomeric (3.6 nm) and the dimeric form (6.9 nm) (Blake, Amin, Qi, Majumda, & Lewis, 2015).…”
Section: Oleic Acid Solubilization In the Presence Of β-Lactoglobulinmentioning
confidence: 98%
“…2 and 4), the decreased signals were detected upon the temperature increasing and thermal transition temperatures (T m ) and onset temperatures (T onset ) of three Raman bands of Phe, Trp, and amide I related to the secondary and tertiary structures were calculated (Tables I and II). The heating tests were also conducted in several studies using Raman spectroscopy and the decreased signals were observed with thermal stress and conformational changes of model proteins were discussed [12,13,15,16]. The T m derived from the respective bands showed almost similar values, indicating that the significant differences were not observed in these experiments.…”
Section: Rituximab Is a Representative Monoclonal Antibody Ofmentioning
confidence: 99%
“…Raman spectroscopy can provide conformational information derived from amino acid residues, especially aromatic ones and secondary structures as demonstrated by analyses of model proteins [10][11][12][13][14][15][16][17]. Spectral changes have been demonstrated to occur upon heating that result from alterations in protein conformation [12,13,15,16,18]. Our group carried out a study for high concentration solutions of an antibody [10].…”
Section: Introductionmentioning
confidence: 99%
“…Typical reported β-LG denaturation temperatures obtained via differential scanning calorimetry (DSC) at high protein concentrations and pH 6.5 to 7.0 range from 73.3 to 75.5°C (Damodaran, 1989;Verheul et al, 1998a;Haug et al, 2009). Higher temperatures are needed to denature β-LG at acidic pH (Haug et al, 2009;Blake et al, 2015).…”
Section: Introductionmentioning
confidence: 99%